The Joy Luck Club - Tan, Amy. (New York : Putnam's, 1989)
In 1949 four Chinese women, recent immigrants to San Francisco, begin meeting to eat dim sum, play mahjong, and talk. United in shared loss and hope, they call themselves the Joy Luck Club. With wit and sensitivity, Amy Tan examines the sometimes painful, often tender, and always deep connection between these four women and their American-born daughters. As each reveals her secrets, trying to unravel the truth about her life, the strings become more tangled, more entwined --
Feathers from a thousand Li away -- The twenty-six malignant gates -- American translation -- Queen mother of the western skies.
Keywords: Chinese American women -- Fiction; Mothers and daughters -- United States -- Fiction; Domestic fiction